Basic Concepts of Learning Evaluation in the Perspective of the Qur'an and Hadith - Jihan In Fatiha; Ainur Rafik; Abd Muhith (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to explore in depth the fundamental concept of evaluation from the perspective of the Qur'an and Hadith, focusing on three main aspects: the definition of learning evaluation in the Qur'an and Hadith, the objectives of learning evaluation in the Qur'an and Hadith, and the principles of learning evaluation derived from these two primary foundations of Islamic teachings. The background of this study stems from the awareness that the evaluation process in education is not merely intended to assess students' learning achievements but also serves as a means of nurturing moral character and strengthening spiritual values in accordance with Islamic law. Therefore, a comprehensive understanding is required of how learning evaluation is positioned within the framework of the values of the Qur'an and Hadith, so that its implementation is not only technical in nature but also embodies moral and spiritual dimensions. This study employs a qualitative approach using a library research method, which involves reviewing, examining, and analyzing data from various relevant primary and secondary literature sources, including Qur'anic exegesis, Hadith commentaries, and scholarly books on Islamic education. The results of the study indicate that learning evaluation from the perspective of the Qur'an and Hadith is not solely oriented toward cognitive learning outcomes but also encompasses affective and psychomotor aspects, emphasizing the formation of Islamic character, honesty, responsibility, and diligence in learning.